Water Quality Index: an Indicator of Surface Water Pollution in Eastern part of Peninsular Malaysia - Nasly, Mohamed Ali; Hossain, Mohamed Amjed; Islam, Mir Sujaul (International Science Congress Association, 2013)
Water quality deterioration in eastern part of peninsular Malaysia especially in Gebeng is the impact of anthropogenic activities due to rapid industrialization. This area is of particular importance in the study of surface water quality because; industrial and municipal wastes, agricultural and run-off from developing areas were mixing with river flow and surrounding water body thereby deteriorating the quality. The aim of the study was to assess the WQI in order to evaluate the water quality of the area for public use, irrigation and other purposes. To fulfill the objectives 240 water samples were collected for 12 months and comprehensive physico-chemical analysis was done using APHA and HACH standard methods of analysis. The WQI was calculated using DOE-WQI based on the concentration of DO, BOD, COD, SS, pH and NH3-N. Results showed the sequence of monitoring stations I4< I3< I2< B2< B3< I1< U1< B1< S2< S1based on WQI value; where the first 8 stations (river part) were categorized as class IV (highly polluted) and the last 2 were classified as class III (polluted). The lowest WQI value was 35.37 and the highest value was 57.53. It was mainly because of low concentration of DO and high concentration of BOD, COD and NH3-N due to the industrial activities. The results indicated that the surface water of the areas was highly polluted and according to the INWQS, Malaysia water of the area cannot be used except irrigation.